From Straightforward Gold(I)-Catalyzed Enyne Cyclizations to more Demanding Intermolecular Reactions of Alkynes with Alkenes - García-Morales, Cristina; Echavarren, Antonio M. (Synlett, 2018)
Gold(I) complexes are the catalysts of choice for the selective activation of alkynes in the presence of other unsaturated functional groups. In this Account, we present the development of gold(I)-catalyzed intermolecular reactions of terminal alkynes with functionalized alkenes. In particular, we focus on the synthesis of cyclobutenes by asymmetric gold(I)-catalyzed [2+2] cycloaddition and its applications.1 Introduction2 Intramolecular Gold(I)-Catalyzed Synthesis of Cyclobutenes2.1 Role of Cyclobutenes in 1,n-Enynes Cycloisomerizations2.2 [2+2] Cycloaddition of 1,n-Enynes3 Intermolecular Gold(I)-Catalyzed Reactions of Terminal Alkynes with Alkenes3.1 [2+2] Cycloaddition of Alkynes with Alkenes3.2 Reactions of Propiolic Acid with Alkenes3.3 [2+2+2] Cycloaddition of Alkynes with Oxoalkenes3.4 Reaction of Alkynes with Furanes4 Gold(I)-Catalyzed Enantioselective Synthesis of Cyclobutenes5 Concluding Remarks
Keywords: gold; alkynes; alkenes; cycloaddition; cyclobutenes; asymmetric catalysis